Mariel of Redwall - Jacques, Brian; Chalk, Gary. (New York : Ace Books, 1991)
The mousemaid Mariel achieves victory at sea for the animals of Redwall Abbey, fighting the savage pirate rat Gabool the Wild, warlord of rodent corsairs.
"Originally published in Great Britain by Hutchinson Children's Books, London"--T.p. verso.